ANALISIS PEMETAAN KESUKAAN KONSUMEN TERHADAP LEMPUK DIKALANGAN MAHASISWA UNIVERSITAS RIAU - Manik, Marjohan '; Restuhadi, Fajar '; Rossi, Evy ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Lempuk durian was a food processed durian fruit that has been popular among the urban community pekanbaru. The number of lempuk durianproducts circulating among the public and the market town of Pekanbaru create different characteristics of each others.This study was conducted to determine the position sensory attributes of the five types of lempuk durianproducts of consumer preferences. This research was done by using internal and external preference mapping. Samples of this study was five commercial products on the market in Pekanbaru. Sensory analysis was done using hedonic and descriptive test involving students of Riau University as a sample of respondents. Sensory attributes were color, elasticity, oily, rancidity, durian aroma, caramel aroma, durian flavor, sweetness and caramel flavor. The results of hedonic test were analysed using Agglomerative Hierarchical Clustering (AHC) and the result descriptive test were analysed using Principle Component Analysis (PCA). The conclusion of this research was the best of lempuk durianwas Asli Bengkalis. Â  Keywords: consumer passions, consumer mapping, sensory attributes, lempuk durian. Â